Exploring the implementation and success of green urban mobility in Asian cities - Sultan, Zahid (Malaysian Institute Of Planners, 2016)
Urban population is rapidly increasing at the rate of 1.83% worldwide. This is accompanied by rise in auto-mobile ownership, which conversely imposes adverse environmental, health, economic and social impact in cities. Green Mobility has emerged as the best approach for promoting sustainable and environmental-friendly transportation in modern cities. This paper relied on secondary data to critically review current transport problems, efforts toward ensuring sustainable green mobility, success of the policies and challenges facing the process in Asian cities. The study found that urban transport problems are becoming worst in the cities. However, efforts are in place to reduce car footprint and promote green mobility in the cities. The global overall average score of cities is estimated at 43.9%, while Asia-Pacific cities have 42.8% average score of green mobility performance. The challenges militating against growth of green mobility in cities include fragmented management, lack of clear vision and strategy for the system, and inadequate infrastructure among others. Integrated and coordinated approach is one of the recommendations made towards ensuring sustainable green mobility in cities.